OPTIMALISASI PENINGKATAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI MELALUI EDUKASI PADA SISWA SEKOLAH MENENGAH ATAS - JANAH, ESTI NUR; Pratama, Daffa Yudha; Zakiyyah, Kholifah Nur; P, Renita Juniyanti Putri; Sopyani, M. Fatih Yakin (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Adolescence is a transition period from children to adults. There are many changes that occur during adolescence, both physical and psychological, so that various problems often arise. Reproductive health problems are still a problem that often arises in teenagers which can be caused by a lack of knowledge about reproductive health among teenagers. For Indonesian society, sexuality is still a taboo issue to discuss so that teenagers do not have access to information about reproductive health. Because education about reproductive health for teenagers is still an important intervention and influences the level of knowledge of teenagers, it is hoped that all teenagers will have excellent reproductive health for a healthy and high-quality generation. The educational participants were 53 students from SMA Negeri 1 Paguyangan who were randomly selected to represent the class. The percentage of teenagers who knew about reproductive health before education was 71% and after education was 98%. There is an increase in knowledge before and after education. Adolescent reproductive health should be material that is routinely given to female students so that knowledge about reproductive health becomes material that is very easily accessible.